Regulating Current Rectification and Nanoparticle Transport Through a Salt Gradient in Bipolar Nanopores. Issue 35 (6th July 2015) - Lin, Chih‐Yuan; Yeh, Li‐Hsien; Hsu, Jyh‐Ping; Tseng, Shiojenn
<x xml:space="preserve">Abstract</x> Tuning of ion and nanoparticle transport is validated through applying a salt gradient in two types of nanopores: the inner wall of a nanopore has bipolar charges and its outer wall neutral (type I), and both the inner and outer walls of a nanopore have bipolar charges (type II). The ion current rectification (ICR) behavior of these nanopores can be regulated by an applied salt gradient: if it is small, the degree of ICR in type II nanopore is more significant than that in type I nanopore; a reversed trend is observed at a sufficiently large salt gradient. If the applied salt gradient and electric field have the same direction, type I nanopore exhibits two significant features that are not observed in type II nanopore: (i) a cation‐rich concentration polarization field and an enhanced funneling electric field are present near the cathode side of the nanopore, and (ii) the magnitude of the axial electric field inside the nanopore is reduced. These features imply that applying a salt gradient to type I nanopore is capable of simultaneously enhancing the nanoparticle capture into the nanopore and reducing its translocation velocity inside, so that high sensing performance and resolution can be achieved.